W06 - Eletro-Metalúrgica Brasileira de Ribeirão Preto - Gonçalves, Pedro Wagner; Sicca, Natalina Aparecida Laguna; de Brino, Marcelo Luis (História da Ciência e Ensino: construindo interfaces, 2017)
EMENTA - WORKSHOP